Les investisseurs étrangers à l’assaut des terres agricoles africaines. - Florence Brondeau (EchoGéo)
The African farmlands are the object of the greed of numerous foreign investors which materializes by an acceleration of the transactions carrying on the concession of lands on a large-scale. These investments correspond to very diverse stakes and give rise to rudimentary contract the exact clauses which are often underestimated. This very mediatized phenomenon is extremely debated and arouses virulent criticisms while the scientific analyses on the subject are still very rare. Towards the anticipated perverse effects and for some already perceptible, he can be perceived as one of the drift of a new agricultural growth model based on the promotion of the agrobusiness.